The count-mass distinction in Hong Kong Sign Language: an intra- and cross-modal comparison - Koenders Emily (Linguistics)
This article is in part an intra- and cross-modal comparison of the count-mass distinction (CMD) in Hong Kong Sign Language (HKSL). For the intra-modal analysis, HKSL data are compared to data found in Koulidobrova’s (2021) work on the CMD in American Sign Language/ASL (Koulidobrova, Elena. 2021. Counting (on) bare nouns: Revelations from American Sign Language. In Tibor Kiss, Francis Jeffry Pelletier & Halima Husić (eds.), Things and Stuff: The Semantics of the Count-Mass Distinction, 213–231. Cambridge: Cambridge University Press). According to Koulidobrova, the existing diagnostics used in spoken language research are insufficient to bring to light CMDs in sign languages. ASL’s CMD is visible in the failure to conjoin count and mass nouns and in the ungrammaticality of partitive constructions containing mass nouns. HKSL and ASL differ from each other in a few respects, among which the two aforementioned ASL diagnostic criteria. Regarding the cross-modal comparison, HKSL and ASL belong to different categories in Chierchia’s (2010) count-mass typology (Chierchia, Gennaro. 2010. Mass nouns, vagueness and semantic variation. Synthese 174. 99–149). Chierchia’s typology is based on CMDs in spoken languages. ASL is a number-neutral language (Type III), whereas HKSL is a number marking language (Type I) and thus patterns with languages like English and Dutch. The CMD in HKSL is visible in its failure to combine mass nouns directly with numerals and count adjectives without the intervention of a classifier. Based on my data analysis, I can furthermore argue that HKSL is a number marking language but that its plural number marking is realised through zero marking.